Orthopedic Trauma: Extremity Fractures. (5th September 2018) - Osier, Charles; Smith, Chris; Stinner, Daniel; Rivera, Jessica; Possley, Daniel; Finnan, Ryan; Bode, Ken; Stockinger, Zsolt
Abstract: Fractures continue to account for a large proportion of combat-related injuries. The basic tenets of irrigation, debridement, soft tissue care, and vigilant monitoring/fasciotomy for acute compartment syndrome persist. Closed management of fractures with splinting or casting is acceptable. If time and facility allow, external fixation of fractures offer many advantages over closed treatment but require knowledge, experience and skill in the safe placement of pins. The care of host nationals presents unique challenges and deployed surgeons must be flexible and resourceful in these situations.